2012
DOI: 10.1038/aps.2012.152
|View full text |Cite
|
Sign up to set email alerts
|

Muscimol microinjection into cerebellar fastigial nucleus exacerbates stress-induced gastric mucosal damage in rats

Abstract: Aim: To investigate the effects of microinjection of the GABA A receptor agonist muscimol into cerebellar fastigial nucleus (FN) on stressinduced gastric mucosal damage and the underlying mechanism in rats. Methods: Stress-induced gastric mucosal damage was induced in adult male SD rats by restraining and immersing them in cold water for 3 h. GABA A receptor agonist or antagonist was microinjected into the lateral FN. The decussation of superior cerebellar peduncle (DSCP) was electrically destroyed and the lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In these etherification reactions, hydroxyl groups in the cellulose chains underwent nucleophilic substitution reactions with the epoxy groups at both ends of PEG, forming the alkoxy groups. In our previous study, we prepared the silk fibroin (SF)/SA composite fiber with a double network using PEGDE as crosslinking agent for SF and CaCl 2 for SA, and found that breaking strength of SF/SA composite fiber was improved by 63.6%. We also demonstrated that addition an appropriate amount of PEGDE could reduce the apparent viscosity of the spinning solution and enhance the spinnability of SF/SA composite fibers.…”
Section: Introductionmentioning
confidence: 99%
“…In these etherification reactions, hydroxyl groups in the cellulose chains underwent nucleophilic substitution reactions with the epoxy groups at both ends of PEG, forming the alkoxy groups. In our previous study, we prepared the silk fibroin (SF)/SA composite fiber with a double network using PEGDE as crosslinking agent for SF and CaCl 2 for SA, and found that breaking strength of SF/SA composite fiber was improved by 63.6%. We also demonstrated that addition an appropriate amount of PEGDE could reduce the apparent viscosity of the spinning solution and enhance the spinnability of SF/SA composite fibers.…”
Section: Introductionmentioning
confidence: 99%
“…We chose anti-PCNA antibodies (diluted to 1:100 with PBS) and the polyHRP anti-rabbit IgG as the primary and the secondary antibod-www.nature.com/aps Li TT et al Acta Pharmacologica Sinica npg ies, respectively [31] . The quantitative analysis was performed blinded under a research microscope (Model IX71, Olympus, Tokyo, Japan).…”
Section: Immunohistochemistry Analysismentioning
confidence: 99%
“…Similarly oral administration of the GABA(A)R agonist abamectin has been demonstrated to be protective against ethanol-induced gastric injury in therat [ 58 ]. However, the injection of the GABA(B)R agonist baclofen or of the GABA(A)R agonist muscimol into cerebellar fastigial nucleus has recently been shown to exacerbate stress-induced gastric mucosal damage in the rat [ 59 , 60 ]. Finally microinjection of L-glutamate into cerebellar interpositus nucleus has recently been shown to prevent gastric ischemia-reperfusion-induced injury in rats and this effect was associated with a significant increase in gastric mucosal blood flow, together with a decrease in gastric cell apoptosis and increase in gastric cell proliferation [ 61 ].…”
Section: Introductionmentioning
confidence: 99%